The Complicated Divorce Petition Process: Services At The Cirebon City Religious Court - Siti Khumayah; Miftahul Jannah; Silvi Riani; Faridah Nurfalah (Edunity Kajian Ilmu Sosial dan Pendidikan, 2024)
Divorce is a complex and sensitive process in Indonesian family law. Therefore, the quality of service in filing divorce applications at the religious court office plays an important role in ensuring justice and welfare for the parties involved. The study aims to evaluate the quality of service in filing divorce applications at the Cirebon City religious court office. The research method used is a qualitative approach, with data collection techniques in the form of direct observation, and interviews with officers and service users. Secondary data in the form of journal books related to research. The informant selection technique used by researchers in this study was the purposive sampling technique. The purposive sampling technique was three key informants, the informants were selected by the researcher to selectively select informants who were relevant to the research objectives. The results showed an evaluation of service quality, there are still obstacles including employees who are less friendly and the process is quite long which affects the quality of service.